الشركات الناشئة وملامح المقاولة في الجزائر: دلائل من مراصد ريادة الأعمال العالمية - عابدي, محمد السعيد (جامعة الوادي - University of Eloued, 2022)
نظراً للطبيعة الفريدة للشركات الناشئة، تقوم منهجية انجاز هذا البحث على: 1. تحليل النتائج التي حققتها الجزائر على مقياس مؤشرات المرصد العالمي لريادة الأعمال خلال الفترة (2015-2019) بهدف التعرف على ملامح قطاع الشركات الناشئة والمقاولة بشكل عام. 2. وصف ما تقوم به السلطات الجزائرية من الجوانب: التشريعية والتنظيمية؛ تنويع مصادر التمويل؛ هياكل الاحتضان والدعم والمرافقة، بهدف استطلاع ما تخصصه الدولة من موارد وما تسخره من إمكانات وهياكل لتسريع نمو هذا القطاع والدفع به لقيادة التحول الاقتصادي نحو المعرفة والتكنولوجيا والنمو المستدام Given the unique nature of start-ups, the methodology of this research is based on: 1. Analyzing the results achieved by Algeria on the indicator scale of the Global Entrepreneurship Monitor during the period (2015-2019) with the aim of identifying the profile of the startups and entrepreneurship sector. 2. Describe what the Algerian authorities are doing in terms of: legislative and regulatory aspects; diversification of funding sources; Structures of incubation, support, and accompaniment, with the aim of exploring the resources allocated by the state and the capabilities and structures to accelerate and drive to the growth of this sector and push it to lead the economic transformation towards knowledge, technology, and sustainable growth
Startups and Entrepreneurship Profiles in Algeria: Evidence from Global Entrepreneurship Monitors
مقال
Keywords: الشركات الناشئة، المقاول، المرسوم التنفيذي 20-254، صندوق الشركات الناشئة الجزائري; Startups, Entrepreneur, Executive Decree 20-254, Algerian Startup Fund